Reactive Oxygen Species and its Manipulation Strategies in Cancer Treatment - Malhotra, Kabil; Malik, Arzoo; Almalki, Waleed H.; Sahebkar, Amirhossein; Kesharwani, Prashant (Current Medicinal Chemistry, 2025)
Cancer is one of the serious diseases of modern times, occurring in all parts of the world and shows a wide range of effects on the human body. Reactive Oxygen Species (ROS) such as oxide and superoxide ions have both advantages and disadvantages during the progression of cancer, dependent on their concentration. It is a necessary part of the normal cellular mechanisms. Changes in its normal level can cause oncogenesis and other relatable problems. Metastasis can also be controlled by ROS levels in the tumor cells, which can be prevented by the use of antioxidants. However, ROS is also used for the initiation of apoptosis in cells by different mediators. There exists a cycle between the production of oxygen reactive species, their effect on the genes, role of mitochondria and the progression of tumors. ROS levels cause DNA damage by the oxidation process, gene damage, altered expression of the genes and signalling mechanisms. They finally lead to mitochondrial disability and mutations, resulting in cancer. This review summarizes the important role and activity of ROS in developing different types of cancers like cervical, gastric, bladder, liver, colorectal and ovarian cancers.
Keywords: Reactive oxygen species (ROS)